2009
DOI: 10.1080/04419057.2009.9674607
|View full text |Cite
|
Sign up to set email alerts
|

Leisure in the Turkish Context: A Preliminary Account

Abstract: The literature on leisure has been dominated by Western examples until recently. Some recent accounts of non-Western cases provide a different and richer context for understanding leisure. This study i s an attempt to reveal the nature and development of leisure in the Turkish context. The historical background of leisure in Turkish society i s briefly presented as on aid to understanding the current situation better. The findings of recent research on time use by Turkish people are also presented with a parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
3
10
0
5
Order By: Relevance
“…For example, research is consistent that less physically active recreation is associated with lower socio-economic status (US Department of Health and Human Services, 1996). Exploratory research in Turkey also confirmed this US finding (Erkip, 2009). Erkip found that physical activity as leisure was mainly for Turkish people with high incomes and more education.…”
Section: Turkish Perspectivessupporting
confidence: 57%
See 4 more Smart Citations
“…For example, research is consistent that less physically active recreation is associated with lower socio-economic status (US Department of Health and Human Services, 1996). Exploratory research in Turkey also confirmed this US finding (Erkip, 2009). Erkip found that physical activity as leisure was mainly for Turkish people with high incomes and more education.…”
Section: Turkish Perspectivessupporting
confidence: 57%
“…Leisure in Turkey appears to have been traditionally considered simply passing time or having empty time without concern for doing particular activities unless related to sports. Erkip (2009) and Aydin (2009) also noted that Turkish perspectives on leisure vary greatly with traditional patterns observed in rural areas and squatter settlements in suburban areas when contrasted to urban areas. Urban areas have typically adopted more Western ways of embodying work and leisure.…”
Section: Turkish Perspectivesmentioning
confidence: 92%
See 3 more Smart Citations